USAGE OF PARAMEDIAN APPROACH FOR CONTINUOUS AMBULATORY PERITONEAL DIALYSIS CATHETER INSERTION TECHNIQUE AND COMPLICATION - Bonar, Ananta; Dahril (Indonesian Urological Association, 2022)
Objective: This study aims to review the usage and complication of paramedian approach for CAPD catheter insertion. Material & Methods: This is a retrospective study. All ESRD patients ongoing CAPD at the Dialysis Clinic of Zainoel Abidin General Hospital in Aceh, Indonesia between January 1, 2009 and December 31, 2018 were included in the present study. Complication outcomes included mechanical and infectious complications are documented and reviewed. Results: A total of 190 ESRD patients had been performed CAPD catheter insertion using paramedian approach in this period. Out of these patients, complication occurred in 31 cases (16.32%). All the complication that occurred in this study are 5 cases of leakage (2.63%), 9 cases of infection (4.74%), 8 cases of drainage problem (4.21%), 9 cases of malposition (4.74%), and no case of bowel perforation. From total of 9 cases of infections, 1 patient had peritonitis from the catheter insertion. The other infection was exit site infection. Conclusion: CAPD catheter insertion using paramedian approach is safe with low complication rates. It could decrease post-operative complications and can be recommended for CAPD catheter insertion technique due to its safety.